2011
DOI: 10.1002/bjs.7347
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre evaluation of intraoperative molecular analysis of sentinel lymph nodes in breast carcinoma

Abstract: OSNA enables accurate automated intraoperative diagnosis and can be used successfully in different UK hospitals. When the SLN is shown to be positive, the patient can undergo immediate axillary clearance under the same anaesthetic rather than having a delayed second procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 35 publications
4
67
2
1
Order By: Relevance
“…19 However, samples from the same node used partly for molecular analysis and partly for morphological analysis generate obvious discrepancies because of uneven tissue distribution. 20 , 21 For example in a previous study, using a fixation procedure that preserved both morphology and high-quality mRNA, we demonstrated, for example, that when metastases >2 mm were located at a pole of a lymph node they might be missed by either hematoxylin & eosin (H&E), immunostaining or RT-PCR applied to samples obtained from the opposite pole of the same lymph node. 21 This data is in line with a previous geometrical model, which showed that incomplete sectioning of the SLNs in extreme situations would almost completely miss metastases >2 mm which would be identified at best as ITC.…”
Section: Reliability Of Whole Sentinel Lymph Node Analysis By Onestepmentioning
confidence: 94%
See 1 more Smart Citation
“…19 However, samples from the same node used partly for molecular analysis and partly for morphological analysis generate obvious discrepancies because of uneven tissue distribution. 20 , 21 For example in a previous study, using a fixation procedure that preserved both morphology and high-quality mRNA, we demonstrated, for example, that when metastases >2 mm were located at a pole of a lymph node they might be missed by either hematoxylin & eosin (H&E), immunostaining or RT-PCR applied to samples obtained from the opposite pole of the same lymph node. 21 This data is in line with a previous geometrical model, which showed that incomplete sectioning of the SLNs in extreme situations would almost completely miss metastases >2 mm which would be identified at best as ITC.…”
Section: Reliability Of Whole Sentinel Lymph Node Analysis By Onestepmentioning
confidence: 94%
“…21 The tissue allocation bias has been regarded as one of the main causes of discordance when comparing the 2 procedures. 20 , 21 However, it has never been discussed whether the micrometastases detected on a sample by molecular assay should be added, for example, to the micrometastases diagnosed by standard histology on the parallel sample of the same SLN to obtain a final evaluation of the tumor burden. These variables may impact heavily on nodal staging of the SLN, because variations in the dimension of the metastasis in the range of microns or a tenth of cells may move a patient from the pN0 (absence of metastases) to the pN1 (presence of metastases) stage and vice versa.…”
mentioning
confidence: 99%
“…Sixteen test accuracy papers were included for OSNA, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] with two papers reporting the same study. Two unpublished papers 40,66 for Metasin were identified and assessed using the Standards for the Reporting of Diagnostic Accuracy Studies (STARD) in Table 7.…”
Section: Number and Description Of Included Studiesmentioning
confidence: 99%
“…Snook et al 61 reported on a UK single-gate, prospective, multicentre evaluation of OSNA involving four centres. In total, 204 patients were recruited, providing 395 SLNs, although there are no further details on recruitment.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation